Transient Energy Reservoir in 2D Perovskites. Issue 22 (20th August 2019) - Gan, Zhixing; Wen, Xiaoming; Zhou, Chunhua; Chen, Weijian; Zheng, Fei; Yang, Shuang; Davis, Jeffrey A.; Tapping, Patrick C.; Kee, Tak W.; Zhang, Hua; Jia, Baohua
Abstract: 2D Ruddlesden−Popper type perovskites have attracted enormous attention due to their natural multiquantum‐well structure. However, there is still mystery regarding the behavior of photocarriers, especially the exciton fine structure behind the excellent optoelectronic performance. The coexistence of two strikingly different decay components in time‐resolved photoluminescence is inconsistent with the high internal quantum yield (QYIN = ≈0.7) in the conventional model for radiative and nonradiative recombinations (QYIN = τnr /(τnr + τr ) = 17%). Here it is revealed that there is a special transient energy reservoir outcompeting nonradiative loss in 2D Ruddlesden−Popper type perovskites. Upon optical excitation, the bright excitons rapidly relax into the low‐lying energy reservoir before nonradiative recombination occurs. Interestingly, the energy in the reservoir is not lost. The carriers in this energy reservoir can spontaneously transfer back to the bright states and can still effectively contribute to the photovoltaic and photonic properties of the perovskites. This investigation provides a novel insight into the mechanism for the lauded defect tolerance of 2D perovskites by highly efficient energy storage via a transient reservoir. Abstract : Anomalous experimental evidences of 2D perovskites from different aspects are presented, which deviate from the general carrier dynamics with irreversible trapping but agree well with the energy reservoir model. A transient energy reservoir mechanism outcompeting nonradiative loss is established in the 2D perovskites, providing a new clue to understand the lauded defect tolerance of perovskites.